2020
DOI: 10.1155/2020/4140692
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Herbal Medicine for Atopic Dermatitis: An Overview of Systematic Reviews

Abstract: Objectives. Herbal medicine (HM) is attracting attention for treating atopic dermatitis (AD). This overview was conducted to summarize and critically evaluate the current systematic reviews (SRs) on HM for the treatment of AD. Methods. Through comprehensive searches, all relevant SRs on HM for AD published until May 2020 were included. The quality of included SRs was assessed using the AMSTAR-2 tool. Moreover, original randomized controlled trials (RCTs) included in the SRs were resynthesized to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Recently, complementary and supportive therapy like herbal medicine, have been reported more frequently and globally. Although evidences are limited, some herbal medicines administered topically and orally effective for treating AD [25]. Orthosiphon aristatus leaves extract is one of important herbal medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, complementary and supportive therapy like herbal medicine, have been reported more frequently and globally. Although evidences are limited, some herbal medicines administered topically and orally effective for treating AD [25]. Orthosiphon aristatus leaves extract is one of important herbal medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Topical calcineurin inhibitors and antihistamine drugs inhibit pruritus in AD patients by T-cell inactivation, but these drugs also cause side effects, including localized burning and stinging [ 25 26 ] . In contrast, herbal medicines efficiently improve AD symptoms and exert fewer side effects [ 27 ] . This study showed that ovalicin alleviates AD symptoms in a DNCB-induced AD mouse model by inhibiting IL-31 signaling and the inflammatory response more than Dexa does.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is toxicity and side effects associateed ewith long-term use of antihistamines, immunosuppressants and local corticosteroids. Therefore, there is a need for new insight and therapeutic materials in the treatment of AD; natural products [25], and herbal medicines [26] have been studied.…”
Section: Discussionmentioning
confidence: 99%